2021
DOI: 10.7759/cureus.16678
|View full text |Cite
|
Sign up to set email alerts
|

Glueless and Sutureless Multi-Layer Amniotic Membrane Transplantation in a Patient With Pending Corneal Perforation

Abstract: Ocular graft-versus-host disease (GVHD) is a severe complication of allogenic hematopoietic stem cell transplantation (HSCT). It is a term used to describe a spectrum of signs and symptoms including ocular surface inflammation, dry eye syndrome, lacrimal and meibomian gland dysfunction. We present a case of a 73-year-old man with chronic myeloblastic leukaemia and chronic GVHD. On examination, severe corneal thinning was detected in his left eye. We performed multi-layer amniotic membrane patching of the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…11 Similarly, healing effect of amniotic membrane described by Lavaris and colleagues support the effectiveness of mAMG in treatment of corneal epithelial defect. 12 The application of BCL over the AM provides better approximation and contact of the AM graft with the corneal surface and protects from retraction of graft with blinking and reduces the duration of healing. Xia Zhang and colleagues reported that the healing time of patients with BCL application over amniotic membrane transplant after pterygium excision was 3.43 ± 1.03 days, as compared to the group without BCL of 5.13 ± 1.16 days.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, healing effect of amniotic membrane described by Lavaris and colleagues support the effectiveness of mAMG in treatment of corneal epithelial defect. 12 The application of BCL over the AM provides better approximation and contact of the AM graft with the corneal surface and protects from retraction of graft with blinking and reduces the duration of healing. Xia Zhang and colleagues reported that the healing time of patients with BCL application over amniotic membrane transplant after pterygium excision was 3.43 ± 1.03 days, as compared to the group without BCL of 5.13 ± 1.16 days.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial recovery and suppression of inflammation may be achieved due to the contained cytokines and growth factors, additionally the amnion membrane acts as a mechanical barrier for frictional forces (184)(185)(186)(187). Indeed, AMT has also successfully been used in progressive corneal ulcers in oGVHD patients (171,(188)(189)(190). However, only limited data are available about its success rate up to now.…”
Section: Amniotic Membrane Transplantation Cyanoacrylate Glue or Conj...mentioning
confidence: 99%
“…Additionally, scleral lenses and bandage soft contact lenses can be used to treat ocular GVHD with a severely refractory ocular surface (62,63). When severe keratitis sicca is resistant to treatment or is complicated by persistent epithelial defects, an amniotic membrane graft can be used to promote epithelialization, suppress inflammation, and reduce subsequent scarring (64)(65)(66). Simultaneously, limbal epithelial transplantation and keratoplasty have also been reported in patients with ocular GVHD (67).…”
Section: Corneal Impairmentmentioning
confidence: 99%